Allantoin accumulation mediated by allantoinase downregulation and transport by Ureide Permease 5 confers salt stress tolerance to Arabidopsis plants - Lescano López, Ignacio (2016)
Allantoin, a metabolite generated in the purine degradation pathway, was primarily considered an intermediate for recycling of the abundant nitrogen assimilated in plant purines. More specifically, tropical legumes utilize allantoin and allantoic acid as major nodule-to-shoot nitrogen transport compounds. In other species, an increase in allantoin content was observed under different stress conditions, but the underlying molecular mechanisms remain poorly understood. In this work, Arabidopsis thaliana was used as a model system to investigate the effects of salt stress on allantoin metabolism and to know whether its accumulation results in plant protection. Plant seedlings treated with NaCl at different concentrations showed higher allantoin and lower allantoic acid contents. Treatments with NaCl favored the expression of genes involved in allantoin synthesis, but strongly repressed the unique gene encoding allantoinase (AtALN). Due to the potential regulatory role of this gene for allantoin accumulation, AtALN promoter activity was studied using a reporter system. GUS mediated coloration was found in specific plant tissues and was diminished with increasing salt concentrations. Phenotypic analysis of knockout, knockdown and stress-inducible mutants for AtALN revealed that allantoin accumulation is essential for salt stress tolerance. In addition, the possible role of allantoin transport was investigated. The Ureide Permease 5 (UPS5) is expressed in the cortex and endodermis of roots and its transcription is enhanced by salt treatment. Ups5 knockout plants under salt stress presented a susceptible phenotype and altered allantoin root-to-shoot content ratios. Possible roles of allantoin as a protectant compound in oxidative events or signaling are discussed.